Associate Teachers' views on dialogic mentoring. Issue 1 (19th May 2021) - Jones, Luke; Tones, Steven; Foulkes, Gethin; Jones, Rhys C.
ABSTRACT: The aim of this paper is to examine Associate Teachers' (ATs) views on dialogic mentoring. More specifically it considers the views of 48 ATs who were involved in an Initial Teacher Education (ITE) partnership that has emerged in response to several changes that have occurred in Welsh education. Educational reforms in Wales have highlighted the value of mentoring and the new ITE partnership is uniquely committed to a dialogic approach. A questionnaire and three focus group interviews were used to generate data from the 48 ATs who were completing a one-year postgraduate programme. Thematic analysis was then used to interrogate the data and identify patterns of response. Adopting a dialogic approach was found to remove some of the anxiety around formal observations and help establish trusting collaborative relationships where ATs were willing to take risks. The dialogic approach was more democratic and gave ATs a stronger voice, but this also created some conflict as mentors' own beliefs were more likely to be questioned. The dialogic approach relied on mentors being fully invested in the process and being committed to open conversations about learning.